Extraction, isolation, characterization, semi-synthesis and antiplasmodial activity of Justicia adathoda leaves (Bangladesh Journal of Pharmacology, 2016)
There is a need to investigate the new sources of antimalarial drugs which are more effective against Plasmodium falciparum. The present study was undertaken to evaluate the in vitro antiplasmodial activity of vasicinone, vasicine and 9-oxo-1, 2, 3, 9-tetrahydropyrrolo [2,1-b]quinazolin-3-yl acetate (VA-1). Vasicinone and vasicine were extracted from the leaves of Justicia adhatoda. The novel compound VA-1 was synthesized from alkaloid the alkaloid vasicine, which was isolated from the ethanol extract of J. adhatoda leaves. Vasicine (IC50 = 89.8 µg/mL) and vasicinone (IC50 = 38.9 µg/mL) showed moderate antiplasmodial activity whereas the compound VA-1 ( IC50  = 06.0 µg/mL) showed excellent antiplasmodial activity when compared with standard drug chloroquine (IC50  = 12.6 µg/mL). The results achieved suggest that both isolated and semi-synthetic compounds may serve as a lead compound to antiplasmodial activity. Further, the compound VA-1 is for the first time reported for antiplasmodial activity with IC50 value.Video Clip of Methodology:Antiplasmodia activity procedure: 7 min 13 sec   Full Screen   Alternative